2020
DOI: 10.21203/rs.3.rs-116775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychiatric Morbidity among Internally Displaced People in Ethiopia

Abstract: Background: Mental health problems in internally displaced people (IDP) can be triggered by either collective effect or individual effect of traumas experienced during Preflight, Flight, and Resettlement time. Higher level of depression and anxiety has been reported among IDPs globally while little is known in Ethiopia.Aims: To assess the prevalence of depression and anxiety among internally displaced people in Gedeo zone, Ethiopia, 2019.Methods: A cross-sectional study was conducted among internally displaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(54 reference statements)
0
0
1
Order By: Relevance
“…This study discovered a link between anxiety and age, employment, education level, and family income. This was in contrast to a study in which age was important but educational level, employment, and current living situation were not [15]. In prior research, however, a lack of a source of income was shown to be strongly related with screening positives for depression and anxiety among IDPs and refugees [16].…”
Section: Discussioncontrasting
confidence: 72%
“…This study discovered a link between anxiety and age, employment, education level, and family income. This was in contrast to a study in which age was important but educational level, employment, and current living situation were not [15]. In prior research, however, a lack of a source of income was shown to be strongly related with screening positives for depression and anxiety among IDPs and refugees [16].…”
Section: Discussioncontrasting
confidence: 72%